Goal, Strategies and Programme of Safe Motherhood in Nepal - Baral, Om Prasad; Vashisth, Kamla (Academic Voices: A Multidisciplinary Journal, 2014)
The safe motherhood programme is one of the priority programme of Nepal. Its primary goal is to reduce maternal and neonatal mortality. Safe pregnancy, safe delivery and safe birth of new born are the major components of safe motherhood. This can be accomplished through increased access to effective antenatal, delivery and postnatal care and a massive health awareness activity in local communities. Academic Voices, Vol. 3, No. 1, 2013, Pages 19-23 DOI: http://dx.doi.org/10.3126/av.v3i1.9981